Optimalisasi Kolaborasi dalam Integrasi Teknologi Sebagai Inovasi Pembelajaran - Mansyur, Abil; Sinaga, Fajar Apollo; Siregar, Tiur Malasari; Frisnoiry, Suci; Elfitra, Elfitra (Jurnal Inovasi Pembelajaran di Sekolah, 2025)
The integration of technology in education is a strategic step toward enhancing the effectiveness and quality of learning in the digital era. Collaboration between academics, teachers, and technology practitioners is a key factor in creating adaptive and effective learning innovations. This study aims to examine the impacts and challenges of optimizing collaboration to support the implementation of technology in education. The research method used is a qualitative approach, with data analysis based on observations, interviews, and document studies from activities focused on strengthening collaboration in technology integration. The findings indicate that effective collaboration can enhance teachers' competence in utilizing technology, enrich students’ learning experiences, and create a more dynamic learning environment. This article recommends strengthening continuous training, improving infrastructure, and establishing academic communities as strategic steps to support the sustainability of technology-based learning innovations.